Meningkatkan Keterampilan Berpikir Kritis Muatan Matematika Menggunakan Kombinasi Model PBL, TTW, DAN CRH - Mahdinatul Khaira; Wahdah Refia Rafianti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
As an educator, determining the right learning model can improve the quality of learning interactions in the classroom. This study was conducted on fifth-grade students of SDN Kuin Utara 5 Banjarmasin which aims to evaluate the effect of implementing a combination of Problem-Based Learning, Think Talk Write, and Course Review Horay models on learning activities, critical thinking skills, and mathematics learning outcomes on the topic "Area of Flat Shapes". Data collection was carried out through critical thinking skills assessments, direct observations, and individual and group written tests. The research findings show that the three learning models are effective in increasing student activity, improving critical thinking skills, and academic learning outcomes. PBL helps students develop systematic learning strategies in solving problems, TTW is able to train oral and written communication skills and improve critical thinking abilities, while CRH strengthens collaboration and makes the classroom atmosphere more enjoyable. The success of implementing these strategies is reflected in the achievement of predetermined indicators.